Textual cohesion in the reality play is a mirror image - Binhanifa, Hind; ELyaboudi, Khalid; Jarrar, Salah; Balajeed, Mariam (Al-Adab Journal, 2023)
This topic, which bears the following title, and is in line with parts of reality, is a ready-made version, the original is by the writer His Highness the Sheikh, and it delves into large parts of the stages of coherence in a play, as it directly carries events in the play Really Arable, as it was talking about The people are trying to find a goal: Peter is looking for Jerusalem but holds a beautiful figure, but it looks like he's trying to turn it down.The problem of the study lies in reaching statistical analyzes of the tools of textual coherence in the reality play Mirror Image, and the research was divided into two chapters, the first is textual coherence at the formal level of the reality play Mirror Image, and the second is textual coherence at the semantic level of the Reality Play Mirror Image.The first contains referral, linking, deletion, and repetition, where I list and describe the sentences that contain these tools; Therefore, the method used in this research is the descriptive statistical method.As for the second, it includes the mechanism of harmony and the relationships included in it, such as semantic relations and others.The reason for choosing this topic is to delve deeper into the linguistics of the text and to research Al-Qasimi's play Reality as a Mirror Image to reveal the relationships that govern it.